Intimate Partner Violence against Women in the EU: A Multilevel Analysis of the Contextual and Individual Impact on Public Perceptions - Karlsson, Matilda (Women & criminal justice, 2022)
Intimate partner violence against women (IPVAW) poses severe threats to women’s health and rights. This study investigates the role of country context and gender equality in shaping individual perceptions of the severity of IPVAW. Multilevel logistic regression analyses of a Eurobarometer survey on attitudes toward IPVAW from 27 EU states showed that male gender, young age, low education, low self-assessed social position and particularly perceiving IPVAW as uncommon were associated with perceiving IPVAW as less severe. The likelihood of perceiving IPVAW as less severe was higher in countries with low gender equality. Between-country variance accounted for 14% of the variability, while country-level gender equality accounted for 22% of the between-country variance. We conclude that efforts toward strengthening perceptions of IPVAW as a severe issue should focus on awareness-raising and on increasing country-level gender equality.